A Review on Analytics Tools and Techniques for E-Commerce - Priya, Y (International Journal of Computer Sciences and Engineering, 2025)
Nowadays the ecommerce play a vital role in our day today life .The knowledge of ecommerce is also a great need for the basic economy in India. The increase in ecommerce is increase the necessity of analyzing to make the virtual stores in India. The commercial E-Commerce platforms and Business owners recognize that, analytics are an integral part of success. Analytics make more than 110,000 e-commerce websites out there which depending revenue of a meaningful scale. That doesn't even include the smaller e-commerce businesses that are new to launch, and growing. They all are competing for the attention of different customer, so it is really need to step up our marketing game to be successful. Using B2C like purchasing and ordering experience in current years as they continue their product discovery and buying behaviors to online and mobile. Research says, in the past decade or so, there have been several changes in consumer behavior .The advantage of sitting at home and comparing prices , features and products has brought new dynamics to the shopping practice the analytics play a crucial role in ecommerce. The paper aims to observe the role of analytics tools in ecommerce and it will make a survey of different business analytical tools available for ecommerce